Peningkatan Ketrampilan Pengrajin Sempe (Gerabah) Melalui Kegiatan Sosialisasi di Negeri Ouw, Kecamatan Saparua, Maluku Tengah - Louhenapessy, William George Mozes (Jurnal Pengabdian Arumbai, 2023)
Negeri Ouw, located in the Saparua District of Central Maluku, has rich cultural and natural potential, particularly in the craft of Sempe pottery. This craft holds high historical and cultural value as a symbol of the community's identity. The potential of Sempe craftsmanship contributes to both the local economy and the preservation of local culture. The enhancement of Sempe craftsmen's skills in Negeri Ouw plays a crucial role in developing the local craft industry and facing market competition. Improved skills help craftsmen understand the market, create product innovations that cater to market demands, and ensure the sustainability of local cultural heritage. The main objective of this community service program is to increase motivation, improve understanding of production techniques, business management, marketing strategies, and product innovation of Sempe in Negeri Ouw. The method used in this activity is socialization, which includes several stages of activities and an evaluation of the achievements and outcomes. The results of the activity show an increase in the competencies of Sempe craftsmen and the competitiveness of their products in the market. The motivation for business increased by 62.7%, indicating the success in motivating the craftsmen. The understanding of production techniques improved by 71.9%, reflecting a better grasp of production methods. The understanding of business management increased by 60.3%, showing improvement in business management skills. The understanding of marketing strategies grew by 62.4%, indicating a better comprehension of marketing approaches. Lastly, the understanding of the importance of product innovation increased by 59.2%.